ENGAGING SIMPLER APPLICATIONS TO DEVELOP STUDENTS’ ENGLISH VOCABULARY AT THE SECONDARY LEVEL - Shandy Purwo; Ramli Ramli; Pangkuh Ajisoko (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Considering the importance of vocabulary in learning English, it was necessary to make efforts to improve students' abilities in developing English vocabulary. The existence of the Simpler application as a medium was expected to make a positive contribution to students. Students' interest in learning while playing can motivate students to actively learn English. This study aimed to improve the development of English vocabulary. This research was experimental research using the pre-experimental method carried out by following the Cresswell research procedure including a pre-test, treatment, and post-test activities. The research was carried out in the first grade of SMPN 7 Tarakan for the academic year 2022/23 consisting of 31 students. The results showed that before giving students treatment using the Simpler application, the average result of the test of students was 48.19, and after 6 meetings using the Simpler application, the result of the final test was an average value of 78.00. The researchers also obtained the results of hypothesis testing using SPSS, whose significance value was smaller than 0.005 and the t value obtained was higher than the t table, 8.488> 1.697, meaning that Ha was accepted. It can be highlighted that the use of the Simpler application in the development of first graders' English vocabulary was very useful.